The Role of KKN-University of Muhammadiyah Sidoarjo Students in Boro Village to Improve Education in Children Through Various Activities Such as Fun Games, Finger Painting, and Spiritual Learning: Peran Mahasiswa KKN-Terpadu Universitas Muhammadiyah Sidoarjo di Desa Boro untuk Meningkatkan Pendidikan Pada Anak Melalui Berbagai Kegiatan Seperti Fun Game, Finger Painting, dan Pembelajaran Rohani (Indonesian Journal of Cultural and Community Development, 2024)
The Integrated Community Service Program (KKN-T) of Universitas Muhammadiyah Sidoarjo in Boro Village aims to improve the quality of children's education through various creative and educational approaches. This program involves several key activities, such as fun games, finger painting, and spiritual learning, designed to develop children's cognitive, motor, and spiritual aspects. The fun games are aimed at enhancing children's social and motor skills, finger painting focuses on fostering creativity and fine motor skills, while spiritual learning is intended to strengthen their religious understanding and moral values. The method used is a participatory approach, where students collaborate directly with the local community in the planning, implementation, and evaluation of the activities. The results of this program show increased participation and motivation of children in learning, both academically and non-academically